Dealing with diversity - Graen, George B. (Emerald Publishing Limited : Information Age Publ., 2003)
Diversity in the workplace has made significant progress in United States companies. Unfortunately, much of the apparent progress has been at the surface level of diversity (Hiller & Day, 2004), where readily visible characteristics identify people of varying genders, ages, ethnicity, and religions. What are needed are prescriptions, based on solid theory and research, that will allow the deep-level diversity to transform well intentioned affirmative action programs from their old reliance on surface-level diversity to a new reliance on deep-level diversity. It is our hope that this volume will stimulate the scholarly activity needed to make progress toward the above stated goal of making deep-level diversity the benchmark of human progress in the workplace.
Keywords: Diversity in the workplace -- United States.; Business & Economics -- Diversity & Inclusion.; Diversity, equality and inclusion in the workplace.; elektronické knihy; electronic books